The effect of root canal treatment and post-crown restorations on stress distribution in teeth with periapical periodontitis: a finite element analysis - ShuoMin Chen; XinHua Hong; ZhangYan Ye; MengHan Wu; Liang Chen; LinMei Wu; Yilin Wang; YuGe Chen; JiaYu Wu; Jun Wang; QinHui Zhang; YuTian Wu; et al. (BMC, 2023)
Abstract Aim To evaluate the effects of root canal treatment (RCT) and post-crown restoration on stress distribution in teeth with periapical bone defects using finite element analysis. Methodology Finite element models of mandibular second premolars and those with periapical bone defects (spherical defects with diameters of 5, 10, 15, and 20 mm) were created using digital model design software. The corresponding RCT and post-crown restoration models were constructed based on the different sizes of periapical bone defect models. The von Mises stress and tooth displacement distributions were comprehensively analyzed in each model. Results Overall analysis of the models: RCT significantly increased the maximum von Mises stresses in teeth with periapical bone defects, while post-crown restoration greatly reduced the maximum von Mises stresses. RCT and post-crown restoration slightly reduced tooth displacement in the affected tooth. Internal analysis of tooth: RCT dramatically increased the maximum von Mises stress in all regions of the tooth, with the most pronounced increase in the coronal surface region. The post-crown restoration balances the internal stresses of the tooth and is most effective in periapical bone defect − 20-mm model. RCT and post-crown restoration slightly reduced the tooth displacement in all regions of the affected tooth. Conclusions Root canal treatment seemed not to improve the biomechanical state of teeth with periapical bone defects. In contrast, post-crown restoration might effectively balance the stress concentrations caused by periapical bone defects, particularly extensive ones.